2021
DOI: 10.21203/rs.3.rs-1069511/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Modified Open-Door Laminoplasty with Reconstruction of the Cervical Posterior Ligamental Complex to Decrease Axial Pain in Cervical Spondylotic Myelopathy

Abstract: Background:Cervical spondylotic myelopathy patients with multiple segments are usually treated with the posterior approach. But expansive open laminoplasty (ELAP) often results in heavy, rigid, and acid bilges feelings in the neck, shoulder, and back, collectively known as axial symptoms. Objective: To evaluate the effect of modified posterior cervical ligament complex reconstruction and single-door laminoplasty with titanium plate fixation on postoperative axial symptoms in patients. Methods: A retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In the 1970s, Hirabayashi et al rst reported the posterior cervical laminoplasty, which is now widely used for the treatment of MCSM, cervical spinal stenosis, and OPLL [11][12] . It has been proven to be a safe and effective surgical technique [13] .…”
Section: Discussionmentioning
confidence: 99%
“…In the 1970s, Hirabayashi et al rst reported the posterior cervical laminoplasty, which is now widely used for the treatment of MCSM, cervical spinal stenosis, and OPLL [11][12] . It has been proven to be a safe and effective surgical technique [13] .…”
Section: Discussionmentioning
confidence: 99%